Administering Topical Eye Drop and Eye Ointment - Shrestha, Romina (Journal of Nursing Education of Nepal, 2011)
Pharmacological application in ophthalmology is extremely important for the treatment and the safety of the patient. Topical instillation of the ophthalmic medication is the major route of drug instillation. It has been indicated almost in all ocular infection and inflammation. Nurses can easily instill, as well as, educate patient and his/her family to instill eye drops and eye ointments. Particularly after the eye surgery when the patient’s vision is so impaired that it is difficult to handle application, it may become necessary for family members to learn how to administer eye drops or ointment. Thus, the objective of this article is to state the steps of administering topical eye drop and eye ointment.
Keywords: N/A